Epidemiological Investigation of Meningeal Worm-Induced Mortalities in Small Ruminants and Camelids Over a 19 Year Period - Keane, Charlena; Marchetto, Katherine M.; Oliveira-Santos, Luiz Gustavo R.; Wünschmann, Arno; Wolf, Tiffany M. (Frontiers in Veterinary Science, 2022)
Meningeal worm, or Parelaphostrongylus tenuis (P. tenuis) is a nematode parasite that can invade the nervous system of small ruminant and camelid species such as alpaca, llama, goats and sheep. Limited reports exist on the epidemiology of disease caused by the nematode in susceptible livestock. We examined archived necropsy reports from small ruminant and camelid mortalities that were submitted, post mortem, to the University of Minnesota Veterinary Diagnostic Laboratory (MNVDL) during 2001-2019 for gross necropsy, histopathology, and pathogen screening. We estimated P. tenuis-induced mortality over time and developed temporal models to better understand patterns and drivers of P. tenuis-induced mortalities in these animals. During the period under examination, 5,617 goats, sheep, llamas and alpacas were necropsied, revealing an overall P. tenuis-induced mortality rate of 1.14% in the necropsy submission pool for these species. P. tenuis-induced mortality rates were highest in llamas (9.91%) and alpacas (5.33%) compared to sheep and goats (<1%), with rates in llamas and alpacas significantly higher than in sheep and goats. P. tenuis-induced mortalities exhibited one seasonal peak, around October to December. P. tenuis-induced mortality rates varied greatly between years, and have significantly increased over time. We also observed a positive correlation between summer temperature (range 20.4-22.4°C) and P. tenuis-induced mortality rates (range 0-3.9%), but not precipitation. This study demonstrates seasonal patterns and differences in mortality between alpacas, goats, llamas and sheep and helps us to better understand the epidemiology of P. tenuis mortality.